2018
DOI: 10.1002/ijc.31388
|View full text |Cite
|
Sign up to set email alerts
|

Is the incidence of advanced‐stage breast cancer affected by whether women attend a steady‐state screening program?

Abstract: In this cross-sectional population-based study, we assessed the incidence of advanced breast cancer based on screening attendance. Women from the Netherlands Cancer Registry were included if aged ≥49 years and diagnosed with breast cancer between 2006 and 2011, and data were linked with the screening program. Cancers were defined as screen-related (diagnosed <24 months after screening) or nonscreened (all other breast cancers). Two cut-offs were used to define advanced breast cancer: TNM-stage (III-IV vs 0-I-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…In recent decennia, mammography screening has been introduced in many countries. Studies have shown that screening can detect breast cancer at an earlier stage which will reduce treatment burden and improve survival [ [2] , [3] , [4] ]. However, there are ongoing debates on whether screening does more harm than good and on the related optimization of screening strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decennia, mammography screening has been introduced in many countries. Studies have shown that screening can detect breast cancer at an earlier stage which will reduce treatment burden and improve survival [ [2] , [3] , [4] ]. However, there are ongoing debates on whether screening does more harm than good and on the related optimization of screening strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The key benefit of regular mammography screening is that it detects breast cancer at an early stage allowing more effective treatment and improved survival [ 2 ]. A recent study showed that the incidence of early-stage breast cancer in patients who attend screening regularly is significantly higher than that in patients who did not, suggesting a stage shift to earlier detection with the implementation of regular screening [ 3 ]. However, there are also controversies regarding screening.…”
Section: Introductionmentioning
confidence: 99%
“…The present study had individual data available for a large cohort of women who regularly responded to three of the biennial invitations of the Germen MSP. It differs from previous study with individual data [4][5][6][7] in that it employedto our knowledge for the first time -the methods suggested by the EU guidelines: the ABC incidence in a cohort of regular screening participants was compared with the reference incidence of ABC in the period prior to the start of the MSP.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, despite large methodological differences (e.g., definition of ABC, definition of screening attender, duration of follow-up, etc. ), all five studies observed reductions in the ABC incidence of screening attenders compared to non-attenders [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation